Crosscheck as a legitimization strategy of the journalism field in reaction to fake news - Trevisan Fossá, Maria Ivete; Müller, Kauane Andressa (Brazilian journalism research, 2019)
ABSTRACT RESUMO RESUMEN tem que pegar no arquivo